2016
DOI: 10.4315/0362-028x.jfp-15-334
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Microbiological Contamination in New York State Produce Fields following Extensive Flooding from Hurricane Irene, August 2011

Abstract: Although flooding introduces microbiological, chemical, and physical hazards onto croplands, few data are available on the spatial extent, patterns, and development of contamination over time postflooding. To address this paucity of information, we conducted a spatially explicit study of Escherichia coli and Salmonella contamination prevalence and genetic diversity in produce fields after the catastrophic flooding that occurred in New England during 2011. Although no significant differences were detected betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Two other studies found a prevalence of 48% in croplands located in or near riparian areas (P.W. Bergholz, unpublished data) and a prevalence of 65% at 248 days after natural flooding in other New York State farms (24).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Two other studies found a prevalence of 48% in croplands located in or near riparian areas (P.W. Bergholz, unpublished data) and a prevalence of 65% at 248 days after natural flooding in other New York State farms (24).…”
Section: Discussionmentioning
confidence: 84%
“…Reports of the prevalence of E. coli in soils of pastures and forests compared to cropland are not entirely new (44,45), though they have been sparse and focused on isolated single-use land areas (3,11,23,24,40). Here, we report a contemporary analysis of E. coli from 1,428 samples collected in an agricultural landscape totaling 585,589 ha.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ultimately, there are no comprehensive prospective studies directly linking microbial contamination of fresh produce to that of hands, soil, water, or surfaces in the natural setting of the agricultural production environment. This may be due to logistical constraints in setting up a matched study design (6,17), resource constraints in acquiring large sample sizes (18), application of the appropriate statistical analyses to account for multivariable factors affecting microbial contamination (6,(19)(20)(21), and data variability from diverse microbial distributions on produce and environmental samples (22)(23)(24). Because of the low rate of detection of pathogen contamination (25)(26)(27)(28), populations of microbial-indicator organisms, including organisms that indicate filth (coliforms) and/or fecal contamination (Escherichia coli, Enterococcus spp., and somatic coliphage), can be monitored (reviewed in references 29 to 31).…”
mentioning
confidence: 99%